A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of leioseius basis and a key for separation of the world species of the genus - Santos, Jandir C. [UNESP]; De Moraes, Gilberto J. (Magnolia Press, 2016)
Leioseius Berlese is known in South America only from one especies described from Chile. Leioseius cananeiensis n. sp. is described based on the morphology of adult females found in association with barnacles (Crustacea, Cirripedia) on roots of Laguncularia racemosa (L.) (Combretaceae) collected in Cananéia, São Paulo State, Brazil. Leioseius basis Karg is redescribed based on the holotype female, one paratype female and two sparatype males. A key for the separation of fe-males of the 19 recognisable world Leioseius species is provided.
Keywords: Ascoidea; Barnacles; Taxonomy